Socioeconomic profile of underegraduate chemistry students: the case od Unesp – Araraquara courses - Agostini, Gabriela [UNESP]; Nascimento, Matheus Monteiro; Massi, Luciana [UNESP] (Soc Brasileira Quimica, 2022)
Considering the recent expansion and democratization of access to Higher Education in Brazil, this article aims to characterize and compare the socioeconomic profiles of students who are entering the Bachelor (BAC), teacher education degree (LIC) and Chemical Engineering (ENG) at UNESP -Araraquara. A quantitative, longitudinal study was performed according to sociological interpretation of Pierre Bourdieu. The data stands for a socioeconomic questionnaire and the performance on the entrance exam of 1544 students between 2003 and 2018. A Socioeconomic Index was built through a Factorial Analysis and a Multiple Correspondence Analysis was performed to compare the profile of students of three courses. The results show that the students' profiles are different, despite becoming similar in recent years, and the demand for these courses has been decreasing since 2016. There are three factors that explain these changes: i) young people's lack of interest in scientific careers; ii) low attractiveness of the teaching career; iii) the creation of a new course modality in the institution (the ENG). Studies like this can contribute to identify, evaluate, and implement actions to democratize the access and permanence of students in Higher Education.
Keywords: Chemistry students; Higher education; Bourdieu; Quantitative study